Assessing contribution of microfinance institutions toward poverty reduction in urban communities a case of mwashita saccos in Dodoma urban - Kayamba, Diana Lucas. (Mzumbe University, 2024)
A dissertation submitted In partial fulfillment of the requirements for award of the Masters of Science In Accounting and Finance